Management of Horizontal Root Fracture in the Middle Third via Intraradicular Splinting Using a Fiber Post - Ishani Karhade; Meenal N. Gulve (Case Reports in Dentistry)
Radicular fractures in permanent teeth are uncommon injuries and account for only 0.5–7% of dental traumas. These fractures commonly result from a horizontal impact and are transverse to oblique in direction. Their incidence is more in the middle third of the root than at the apical and cervical thirds. This paper describes a case of complicated crown fracture of maxillary incisors along with horizontal root fracture at the middle third of maxillary right central and lateral incisor. The fractured root fragments of the upper right central and lateral incisor were united with the help of a glass fiber post after receiving an endodontic treatment. The other two incisors were treated endodontically followed by post endodontic restorations. Eventually the four incisors were restored with porcelain fused to metal crowns. A one-year follow-up revealed a well stabilized assembly of the root fragments and the post.